The Impact of Cashless Payment Policies on Consumer Behavior at Kesiangan Coffee, Batam City - Brightness Bill Boy N; Syafruddin Rais (CV. Publikasi Indonesia, 2024)
This research aims to analyze the effect of cashless payment policy on consumer behavior at Kesiangan Coffee, Batam City. With the increasing use of technology in various aspects of life, especially in the payment sector, it is important to understand how cashless policies affect consumer behavior. This study used a survey method with questionnaires distributed to 100 respondents. Data analysis was conducted using SPSS software, and it included validity, reliability, and linear regression analysis. The results showed that the R-value was 0.128 and the R Square was 0.165, indicating that only 16.5% of the variation in the cashless payment policy could be explained by consumer behavior. The validity and reliability test results show that all research instruments are valid and reliable, but the influence of consumer behavior on this policy is still relatively low. This finding suggests that other more dominant factors, such as technological infrastructure, level of security, and consumer demographics, influence the acceptance of cashless payments. Therefore, it is recommended that relevant parties, such as financial institutions and the government, focus on education and infrastructure development to increase the acceptance of this payment system among the public. Further research is needed to explore other factors that play a role in influencing cashless payment policies, so that more effective strategies can be implemented to encourage the use of this technology in various sectors.